Answer:
![b=-3](https://tex.z-dn.net/?f=b%3D-3)
Step-by-step explanation:
The given function is
.
When we compare to
, we have
and c=10
The equation of the axis of symmetry of a vertical parabola is:
![x=-\frac{b}{2a}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7Bb%7D%7B2a%7D)
Also from the question the axis of symmetry is x=6
We substitute the values to get:
![6=-\frac{b}{2*\frac{1}{4}}](https://tex.z-dn.net/?f=6%3D-%5Cfrac%7Bb%7D%7B2%2A%5Cfrac%7B1%7D%7B4%7D%7D)
![6=-\frac{b}{\frac{1}{2}}](https://tex.z-dn.net/?f=6%3D-%5Cfrac%7Bb%7D%7B%5Cfrac%7B1%7D%7B2%7D%7D)
![b=-\frac{1}{2}*6](https://tex.z-dn.net/?f=b%3D-%5Cfrac%7B1%7D%7B2%7D%2A6)
![b=-3](https://tex.z-dn.net/?f=b%3D-3)
Answer:
4.5
Step-by-step explanation:
Answer:
He switched the divisor and the dividend when creating an equation to model the problem in step 1.
Step-by-step explanation:
got it right on edgenity quiz
Hello,
Using vectors and scalar product:
![[(a+c)*\vec{i}+(b-0)*\vec{j} ].[(a-c)*\vec{i}+(b-0)*\vec{j}]=0](https://tex.z-dn.net/?f=%5B%28a%2Bc%29%2A%5Cvec%7Bi%7D%2B%28b-0%29%2A%5Cvec%7Bj%7D%20%5D.%5B%28a-c%29%2A%5Cvec%7Bi%7D%2B%28b-0%29%2A%5Cvec%7Bj%7D%5D%3D0%20)
Thus
![\dfrac{b^2}{(a+c)(a-c)}=1](https://tex.z-dn.net/?f=%5Cdfrac%7Bb%5E2%7D%7B%28a%2Bc%29%28a-c%29%7D%3D1%20)
By the way how can we make text larger in latex \larger{.....} don't work.
Answer A